Waste management: accounting problem - Kremenovska, I.V. (Математичне моделювання в економіці, 2017)
The research is devoted to the survey of statistical data in the sphere of solid waste utilization and recycling in different regions of Ukraine. In the article cited information as to amount, volume and morphological composition of solid waste products based on information received from local authorities of cities are regional centers of Ukraine (except for the temporarily occupied areas of Donetsk and Lugansk regions and the Autonomous Republic of Crimea). Based on the analysis of the reporting approaches that have developed in different cities, shown existence of significant differences and discrepancy between some accounting indicators that influence on the state work of mass counting and amount of solid waste products, and determination of their morphological composition. Formulated proposals for unification of the approach to the implementation of the accounting of quantitative and qualitative indicators of solid waste products, which will help to more accurately to determine their volume, mass and composition to increase the efficiency of their utilization measures. Дослідження присвячено оглядові статистичних даних у сфері утилізації та переробки твердих побутових відходів у різних областях України. У статті наведено відомості щодо кількості, обсягу та морфологічного складу твердих побутових відходів за інформацією, одержаною від органів місцевого самоврядування міст, які є обласними центрами України (за винятком території тимчасово окупованих окремих районів Донецької та Луганської областей і Автономної Республіки Крим). На підставі аналізу підходів до формування звітності, які склалися у різних містах, показано наявність суттєвих розбіжностей й невідповідності деяких облікових показників, які впливають на стан роботи зі здійснення обрахування маси та обсягу твердих побутових відходів, а також визначення їх морфологічного складу. Сформульовано пропозиції щодо уніфікації підходу до здійснення обліку кількісних і якісних показників твердих побутових відходів, що сприятиме більш точному визначенню їх обсягу, маси та складу для підвищення ефективності заходів з їх утилізації. Исследование посвящено обзорные статистических данных в сфере утилизации и переработки твердых бытовых отходов в разных областях Украины. В статье приведены сведения о количестве, объема и морфологического состава твердых бытовых отходов по информации, полученной от органов местного самоуправления городов, которые являются областными центрами Украины (за исключением территории временно оккупированных отдельных районов Донецкой и Луганской областей и Автономной Республики Крым). На основании анализа подходов к формированию отчетности, сложившиеся в разных городах, показано наличие существенных разногласий и несоответствия некоторых учетных показателей, влияющих на состояние работы по осуществлению расчета массы и объема твердых бытовых отходов, а также определение их морфологического состава. Сформулированы предложения по унификации подхода к осуществлению учета количественных и качественных показателей твердых бытовых отходов, что будет способствовать более точному определению их объема, массы и состава для повышения эффективности мер по их утилизации.